IMPACT OF SOCIAL RESPONSIBILITY DISCLOSURE ON THE INTEGRATION OF GREEN ACCOUNTING AND CORPORATE GOVERNANCE ON HIGHLY POLLUTED INDUSTRIES IN INDIA - Tanwar, Jyoti; Rao, NVM (International Journal of Accounting & Finance Review, 2023)
Fulfilment of environmental and social obligations is required for sustainable development. Green accounting integrates all environmental consequences into corporate accounting accounts. Disclosure of Corporate social responsibility is a component of accounting performance tied to the social, economic, and environmental aspects of a company’s programme that can be vital in cultivating stakeholders. The current research aims to investigate the effect of social responsibility disclosure on integrating green accounting and corporate governance of highly polluting industries in India. The study employed a descriptive study design and qualitative research methods in accordance with the interpretative research philosophy and collected the sample data from 52 highly polluted industries from Central Pollution Board in India. The study employs a structural model, descriptive statistics, and F-test analysis. The result reveals that green accounting and firm characteristics significantly enhance the selected firms’ social responsibility disclosure. Furthermore, it was discovered that corporate governance and social responsibility disclosure impact the chosen firms’ performance and value. However, it has been determined that green accounting does not affect the profitability or market value of the selected firms. Also, this work concludes that a good firm gives its surroundings and surrounding community enough consideration in addition to its pursuit of profit. As the research is based on 52 industries, the generalized result can not bed determined. The knowledge of the respondent also impacts the research. JEL Classification Codes: M49, M14, G30, Q56.